Implementation of Budgetary Policy for Stunting Management in Wangurer Village, South Likupang District, Indonesia - Fransye D. Talumantak; Steven V. Tarore; Laurens L. Bulo (International Journal of Information Technology and Education, 2026)
This article develops a journal-style reconstruction of Fransye David Talumantak’s thesis on the implementation of budgetary policy for stunting management in Wangurer Village, South Likupang District, North Minahasa Regency, Indonesia. The study focuses on the procurement and distribution of supplementary feeding (PMT) financed through village funds and analyzes the determinant factors shaping implementation quality. Using a qualitative descriptive design, the original thesis gathered data through in-depth interviews, observation, and document analysis involving the village head, village secretary and finance officer, the chair of the village women’s movement, posyandu cadres, health workers from the local health center, community figures, and families with children at risk of stunting. The article reorganizes the thesis into a journal manuscript modeled on the structure of the Sammy article supplied by the user while preserving the empirical substance of the original research. The findings show that the policy has been implemented procedurally through budget allocation, budget utilization, food procurement, monthly distribution, and field assistance. Stunting has been recognized as a priority in the village budget and discussed through participatory village deliberation. Nevertheless, implementation remains only partially effective. Budget decisions are still dominated by administrative logic rather than detailed nutritional evidence; the quality of supplementary food is shaped not only by technical health considerations but also by local bargaining in village meetings; distribution is highly dependent on budget disbursement; beneficiary validation and household-level monitoring remain weak; and supervision is still largely administrative rather than performance-based. Four determinant factors stand out: budget governance, technical nutritional capacity, distribution and targeting mechanisms, and collaboration plus supervision across actors. The article argues that village-level stunting policy cannot be judged only by budget absorption or formal compliance. Its effectiveness depends on whether financial planning, nutrition expertise, targeting accuracy, cross-sector coordination, and community oversight are integrated into one implementation system. Strengthening should therefore focus on evidence-based budgeting, continuous cadre training, flexible and data-based distribution, structured monitoring of food consumption, and participatory accountability mechanisms. The study contributes to public administration literature by showing that village fund policy for stunting reduction is not merely a fiscal question, but a governance issue involving implementation capacity, local politics, intersectoral coordination, and community trust.